Družba v slovenski dramatiki pod socializmom in danes - Troha, Gašper (Primerjalna književnost, 2019)
The article compares two dramas by Dušan Jovanović and Simona Semenič. The first is Military Secret (1983) and the second nineteeneighty-one (2013), both describing the last decade of socialist Yugoslavia. What strikes us as odd is the fact that the image of socialist society in both texts differs to quite an extent. Jovanović describes it as a radical dystopia in the form of the drama of the absurd, and Semenič as a utopian or nostalgic image of an epoch when ethics was still present in human relations. However, the analysis shows that Semenič is using this image of socialism to emphasize the dystopia of the modern neoliberalism of contemporary Slovenia. Furthermore, she uses an innovative form of montage with dream-like flash-forwards into the future, to provoke the reader's/viewer's emotions and her intellectual response. She unsettles reception in the manner of post-dramatic theatre as understood by Hans Thies Lehmann in order to build her social criticism of contemporary human condition. Jovanović, on the other hand, camouflages his social critique in the form of the theatre of the absurd. He sets it in a zoolinguistic institute where animals enact some of the absurd patterns of self-government (e.g. an election process with only one candidate, constant search for compromise, an impossible economy). Military Secret was a result of the special position of Slovenian theatre in the 1980s when theatre was understood as a social forum, a place where dissident ideas could be discussed. nineteeneighty-one echoes a different social situation, in which we are constantly bombarded with information in a mediatised world. In this new reality, an author needs to invent new forms in order to stimulate an emotional and intellectual response that will be able to convey the social critique of a theatrical piece.
Keywords: Jovanović, Dušan: Vojaška skrivnost; književnost in družba; politično gledališče; Semenič, Simona: tisočdevetstoenainosemdeset; socializem; sodobna slovenska dramatika